Invisible emotional expressions influence social judgments and pupillary responses of both depressed and non-depressed individuals - Laeng, Bruno; Sæther, Line; Holmlund, Terje; Wang, Catharina Elisabeth A.; Waterloo, Knut; Eisemann, Martin; Halvorsen, Marianne (Frontiers in Psychology, 2013)
We used filtered low spatial frequency images of facial emotional expressions (angry, fearful, happy, sad or neutral faces) that were blended with a high-frequency image of the same face but with a neutral facial expression, so as to obtain a “hybrid” face image that “masked” the subjective perception of its emotional expression. Participants were categorized in three groups of participants: healthy control participants (N= 49), recovered previously depressed (N= 79), and currently depressed individuals (N= 36), All participants were asked to rate how friendly the person in the picture looked. Simultaneously we recorded, by use of an infrared eye-tracker, their pupillary responses. We expected that depressed individuals (either currently or previously depressed) would show a negative bias and therefore rate the negative emotional faces, albeit the emotions being invisible, as more negative (i.e., less friendly) than the healthy controls would. Similarly, we expected that depressed individuals would overreact to the negative emotions and that this would result in greater dilations of the pupil’s diameter than those shown by controls for the same emotions. Although we observed the expected pattern of effects of the hidden emotions on both ratings and pupillary changes, both responses did not differ significantly among the three groups of participants. The implications of this finding are discussed.